Highly Efficient Perovskite‐Quantum‐Dot Light‐Emitting Diodes by Surface Engineering. Issue 39 (16th August 2016) - Pan, Jun; Quan, Li Na; Zhao, Yongbiao; Peng, Wei; Murali, Banavoth; Sarmah, Smritakshi P.; Yuan, Mingjian; Sinatra, Lutfan; Alyami, Noktan M.; Liu, Jiakai; Yassitepe, Emre; Yang, Zhenyu; et al.
Abstract : A two‐step ligand‐exchange strategy is developed, in which the long‐carbon‐ chain ligands on all‐inorganic perovskite (CsPbX3, X = Br, Cl) quantum dots (QDs) are replaced with halide‐ion‐pair ligands. Green and blue light‐emitting diodes made from the halide‐ion‐pair‐capped quantum dots exhibit high external quantum efficiencies compared with the untreated QDs.